Contingency Teaching During Close Reading. (5th August 2014) - Fisher, Douglas; Frey, Nancy
Abstract: 12 teachers were interviewed and observed as they engaged students in close reading. We analyzed their responses and instruction to determine the scaffolds that were used as well as the contingency teaching plans they implemented when students were unable to understand the text.